A meta‐analysis of tract‐based spatial statistics studies examining white matter integrity in cocaine use disorder. (8th April 2020) - Suchting, Robert; Beard, Charlotte L.; Schmitz, Joy M.; Soder, Heather E.; Yoon, Jin H.; Hasan, Khader M.; Narayana, Ponnada A.; Lane, Scott D.
Abstract: Tract‐based spatial statistics (TBSS) of diffusion tensor imaging (DTI) studies have consistently shown diminished white matter (WM) integrity for individuals with cocaine use disorder (CUD). The present study used seed‐based d mapping (SDM) to determine the extent to which a systematic difference in the WM integrity of cocaine users may exist (as compared with that of healthy controls). Articles from 2006 (when TBSS was first developed) to present were reviewed, with eight selected for inclusion. Meta‐analysis found lower fractional anisotropy (FA) in the genu of the corpus callosum for cocaine users, with a small‐to‐moderate peak effect size (Hedge's g = −0.331). Sensitivity analyses mostly supported the robustness of the obtained difference. Differences detected at exploratory thresholds for significance suggested insult to WM integrity extending beyond the corpus callosum. The present results compliment a previous region‐of‐interest (ROI)‐based meta‐analysis of DTI studies in individuals with CUD. These findings have significant implications for the potential role of neuroprotective agents in the treatment of CUD and merit additional iteration as more studies accrue in the literature. Abstract : Several studies using tract‐based spatial statistics (TBSS) have shown diminished white matter (WM) integrity for individuals with cocaine use disorder. Meta‐analysis via seed‐based d mapping (SDM) found lower fractional anisotropy (FA) in the genu of the corpus callosum for cocaine users, with a small‐to‐moderate peak effect size (Hedge's g = −0.331). Exploratory follow‐up analyses suggested insult to WM integrity extending beyond the corpus callosum.